Ca-mediated alleviation of Cd²⁺ induced toxicity and improved Cd²⁺ biomineralization by Sporosarcina pasteurii - Fang, Longyang (2022)
Microbial induced carbonate precipitation has been widely used in the biomineralization of heavy metals Cd2+. However, the low Cd-tolerance of ureolytic bacteria limits the applications with only low Cd2+concentrations. In this study, we discovered a simple approach to significantly enhance the Cd2+ resistance of ureolytic bacteria through an immediate supplement of Ca2+. The Ca2+ protected the cells by reducing the extracellular and intracellular Cd2+ concentration by about 50%. As a result, the Cd2+ removal efficiency was notably improved by about 100% (52.72% to 99.43%, Cd = 5 mM) with Ca2+ supplement. Moreover, extremely high concentration of Cd2+ could be almost completely removed (99.46% at C0 = 20 mM and 99.60% at C0 = 50 mM) within 24 h. Microstructure analyses indicated that the mineralized precipitates were rhombohedral-shaped CdCO3, CaCO3, and (Ca0.67, Cd0.33)CO3. Furthermore, Ca2+ could also protect ureolytic bacteria against toxicity from other heavy metals.